Education for digital libraries in Asian countries - Abu Bakar, Ahmad Bakeri (2009)
This paper looks at the state of education in digital libraries in Asian countries. Academic programs offered at the post graduate level by the Department of Library and Information Science or other Departments which can be categorized as similar or equivalent to the Department of Library and Information Science were surveyed in all the countries of Asia. Method: The survey was conducted on the library and information science programs that are able to be accessed through the open web based on the course titles and synopsis. Analysis on fifty one library and information science programs from all countries of Asia was performed on the basis of two limiting criteria. Firstly it should be in a language comprehended by the author and using the phrase “digital library” or “digital libraries”; secondly the programmes should be at postgraduate level. Results: There are eight countries that are offering independent digital library courses through their academic institutions, namely India, Indonesia, China, South Korea, Malaysia, Hong Kong, Taiwan and Thailand.. Academic institutions from four other countries are offering integrated digital library courses namely Malaysia, Singapore, Taiwan and Japan. Conclusion: The number of academic institutions that are offering digital library education in Asia are really few as compared to their number globally. It can be concluded that countries that have reached a certain economic level are inspired to offering digital library education. It will not be out of context judging from the results of this study that there is a relationship between level of ICT development in a country with the willingness to offer digital library education